Self-Assembly of [3]Catenane and [4]Catenane Based on Neutral Organometallic Scaffolds - Wu, Gui-Yuan; Zhu, Hong-Juan; Pan, Fang-Fang; Sheng, Xiao-Wei; Zhang, Ming-Rui; Zhang, Xianyi; Yao, Guangxin; Qu, Hang; Lu, Zhou (Frontiers in Chemistry, 2021)
Transition metal-mediated templating and self-assembly have shown great potential to construct mechanically interlocked molecules. Herein, we describe the formation of the bimetallic [3]catenane and [4]catenane based on neutral organometallic scaffolds via the orthogonality of platinum-to-oxygen coordination-driven self-assembly and copper(I) template–directed strategy of a [2]pseudorotaxane. The structures of these bimetallic [3]catenane and [4]catenane were characterized by multinuclear NMR {1H and 31P} spectroscopy, electrospray ionization time-of-flight mass spectrometry (ESI-TOF-MS), and PM6 semiempirical molecular orbital theoretical calculations. In addition, single-crystal X-ray analyses of the [3]catenane revealed two asymmetric [2]pseudorotaxane units inside the metallacycle. It was discovered that tubular structures were formed through the stacking of individual [3]catenane molecules driven by the strong π–π interactions.